Single-cell transcriptomic and cell‑type‑specific regulatory networks in Polima temperature-sensitive cytoplasmic male sterility of Brassica napus L. - Shipeng Li; Jing Zhang; Caiwu Chen; Ahmad Ali; Jing Wen; Cheng Dai; Chaozhi Ma; Jinxing Tu; Jinxiong Shen; Tingdong Fu; Bin Yi (BMC Plant Biology)
Abstract Background Thermosensitive male sterility (TMS) is a heritable agronomic trait influenced by the interaction between genotype and environment. The anthers of plants are composed of various specialized cells, each of which plays different roles in plant reproduction. In rapeseed (Brassica napus L.), Polima (pol) temperature-sensitive cytoplasmic male sterility (TCMS) is widely used in two-line breeding because its fertility can be partially restored at certain temperatures. The pol-TCMS line exhibits abnormal anther development and pollen abortion at high (restrictive) temperatures (HT, 25 °C) compared to at low (permissive) temperatures (LT, 16 °C). However, the response of different anther cell types to HT and the dynamic regulation of genes under such conditions remain largely unknown. Results We present the first single-cell transcriptomic atlas of Brassica napus early developing flower bud tissues in response to HT. We identified 8 cell types and 17 transcriptionally distinct cell clusters via known marker genes under LT and HT treatment conditions. Under HT conditions, changes in the gene expression patterns of different cell clusters were observed, with the number of down-regulated genes in various cell types exceeding that of up-regulated genes. Pseudotime trajectory analysis revealed that HT strongly affected the development of early stamen/anther tissue cells. In combination with the snRNA-seq, WGCNA, and bulk RNA-seq results, we found that many transcription factors play crucial roles in the response to HT, especially heat response family genes. Conclusions Our study revealed the transcriptional regulatory network of floral bud tissue in the pol-TCMS line under HT/LT conditions and increased our understanding of high-temperature-induced anther developmental abnormalities, which may help researchers utilize TCMS in the two-line breeding of Brassica plants.